Market-Based Health Care in Specialty Surgery: Finding Patient-Centered Shared Value. Issue 4 (25th June 2015) - Smith, Timothy R.; Rambachan, Aksharananda; Cote, David; Cybulski, George; Laws, Edward R.
Abstract: The US health care system is struggling with rising costs, poor outcomes, waste, and inefficiency. The Patient Protection and Affordable Care Act represents a substantial effort to improve access and emphasizes value-based care. Value in health care has been defined as health outcomes for the patient per dollar spent. However, given the opacity of health outcomes and cost, the identification and quantification of patient-centered value is problematic. These problems are magnified by highly technical, specialized care (eg, neurosurgery). This is further complicated by potentially competing interests of the 5 major stakeholders in health care: patients, doctors, payers, hospitals, and manufacturers. These stakeholders are watching with great interest as health care in the United States moves toward a value-based system. Market principles can be harnessed to drive costs down, improve outcomes, and improve overall value to patients. However, there are many caveats to a market-based, value-driven system that must be identified and addressed. Many excellent neurosurgical efforts are already underway to nudge health care toward increased efficiency, decreased costs, and improved quality. Patient-centered shared value can provide a philosophical mooring for the development of health care policies that utilize market principles without losing sight of the ultimate goals of health care, to care for patients.